The Hazard Content of Cadmium, Lead, and Other Trace Elements in Some Medicinal Herbs and Their Water Infusions - Fuad A. Ababneh (International Journal of Analytical Chemistry)
54 samples belonging to 23 herbal species (15 individuals and 8 mixtures) were analyzed for their contents of heavy metals in the raw materials and in their water infusions. Trace and toxic elements in these samples were determined by using inductively coupled plasma-atomic emission spectrometry (ICP-OES) following acid digestion. The order of decreasing mean metal concentrations in raw materials (mg/kg) was found to be as follows: Fe (440) > Mn (162) > Zn (45.8) > Cu (12) > Pb (10.4) > Ni (5.4) > Cr (2.9) > Co (0.91) > Cd (0.5). It was found that 21% of the analyzed samples contain both Cd and Pb above their permissible limits. However, the infusions produced from these plants were found to contain fewer amounts of metals than the raw materials. Studied metals had the following mass transfer percentages to the infusion solutions (Fe: 3.5%, Cd: 14%, Cr: 15%, Pb: 20%, Co: 29%, Ni: 31%, Zn: 36%, Cu: 48%, and Mn: 53%). The estimated daily intake calculated for the toxic elements Pb and Cd through the consumption of herbal infusions was far below the tolerable daily intake set by the World Health Organization (WHO).